2011
DOI: 10.1111/j.2042-3292.2011.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of injection techniques targeting the sacroiliac region in horses

Abstract: Summary Local anaesthetic techniques and diagnostic imaging tools are currently used in conjunction with thorough physical and lameness examinations to diagnose sacroiliac disease (SID) in the horse. The deep and inaccessible location of the sacroiliac joint (SIJ), however, often renders diagnostic imaging modalities, such as radiography, nuclear scintigraphy and ultrasonography, unreliable in identifying sacroiliac problems. The equine clinician therefore often has to rely on positive results of local anaesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Diagnostic analgesia can confirm the presence of pain in the sacroiliac joint region . However, this is a nonspecific block and there is potential for local anesthetic solution to diffuse around the dorsal sacroiliac ligaments and the lumbosacral joints . There are likely to be several different pathological processes that can cause pain in the sacroiliac joint region, which may explain the observation of moderate sensitivity and specificity of increased radiopharmaceutical uptake for final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic analgesia can confirm the presence of pain in the sacroiliac joint region . However, this is a nonspecific block and there is potential for local anesthetic solution to diffuse around the dorsal sacroiliac ligaments and the lumbosacral joints . There are likely to be several different pathological processes that can cause pain in the sacroiliac joint region, which may explain the observation of moderate sensitivity and specificity of increased radiopharmaceutical uptake for final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…33 However, this is a nonspecific block and there is potential for local anesthetic solution to diffuse around the dorsal sacroiliac ligaments and the lumbosacral joints. 47,[56][57][58] There are likely to be several different pathological processes that can cause pain in the sacroiliac joint region, which may explain the observation of moderate sensitivity and specificity of increased radiopharmaceuti-cal uptake for final diagnosis. In a recent study of horses with sacroiliac joint region pain (as confirmed by a positive response to infiltration of local anesthetic solution around the sacroiliac joint regions), only 72/167 (43%) had increased radiopharmaceutical uptake.…”
Section: Hocks and Sacroiliac Jointsmentioning
confidence: 99%
“…). Ultrasound‐guided injection of the SI joint region has been described (Denoix and Jacquet ); however, the cranial approach is effectively blind once the needle has passed under the ilial wing and the caudal approach risks damage to neurovascular structures (Engeli and Haussler , ) and sciatic nerve paralysis. The dramatic clinical improvements following SI block demonstrate the high level of discomfort experienced by many horses with SI joint region pain.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is recognised that this analgesic technique is not specific for the SI joints, and can influence closely related anatomical structures (Dyson and Murray ; Engeli et al . ; Engeli and Haussler ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation